(untitled) (Biological Sciences - PJSIR, 2003)
Rafiqius bodenheimeri (Steiner 1936) Khan and Hussain 1998 Discolaimus lahorensis are described from Karachi, R. bodenheimeri (Steiner 1936) Khan and Hussain 1998 is different in size and shape of post vulval uterine sac which is being 70.2?m in length, whereas, uterine sac is collapsed in R. saeedi. Males are present, in R. bodenheimeri while males not found in R. saeedi. R. bodenheimeri is different from R. amurensis (Truskova 1971, Siddiqi, Deley and Khan 1992) Khan and Hussain 1998 in body length, shape of spicules and size of gubernaculum.